2015
DOI: 10.1016/j.jnucmat.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cr on the interdiffusion between Ce and Fe–Cr alloys

Abstract: openAccessArticle: Falsecover date: 2015-03-01pii: S0022-3115(14)00977-5Harvest Date: 2016-01-06 13:08:32issueName:Page Range: 264-264href scidir: http://www.sciencedirect.com/science/article/pii/S0022311514009775pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The bounding surface was rubbed on a clean napped polishing pad to fully remove oxides, which is similar with the process in Ref. [17]. Note that the polishing process that running with water and diamond paste were not applied in this work, as water would rapidly oxidize cerium.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…The bounding surface was rubbed on a clean napped polishing pad to fully remove oxides, which is similar with the process in Ref. [17]. Note that the polishing process that running with water and diamond paste were not applied in this work, as water would rapidly oxidize cerium.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…The smaller diffusion depth in the Ce side in the present study is due to the Cr in HT9. A previous study on the interdiffusion between Ce and the 12Cr-Fe wt% alloy suggested that when Ce diffuses into the alloy, interacting with Fe, the Cr present would segregate and precipitate into a Cr-rich σ phase composed of Cr and Fe [31]. Because the σ-(Cr, Fe) phase consumes some of the available Fe at the interface, less Fe is available to diffuse into Ce, therefore slowing down the diffusion of Fe into Ce.…”
Section: Ht9/ce and Fe/cementioning
confidence: 99%